Adaptations to HIV services delivery amidst the COVID-19 pandemic restrictions in Kampala, Uganda: A qualitative study. - Jonathan Izudi; Agnes N Kiragga; Stephen Okoboi; Francis Bajunirwe; Barbara Castelnuovo (PLOS Global Public Health, 2022)
The enforcement of the coronavirus disease (COVID-19) pandemic restrictions disrupted health services delivery and currently, there is a limited understanding regarding measures employed by health facilities to ensure delivery of human immunodeficiency virus (HIV) services amidst the interruptions. We, therefore, designed a qualitative study to explore the measures for continuity of HIV services during the COVID-19 pandemic restrictions in Kampala, Uganda. This study was conducted at six large primary health care facilities in the Kampala Metropolitan area. Qualitative data were collected from anti-retroviral therapy (ART) focal persons and lay health workers namely linkage facilitators and peer mothers through key informant interviews (KIIs). Overall, 14 KIIs were performed, 10 with lay health workers and 4 with ART focal persons. Data were audio-recorded, transcribed verbatim, and analyzed using the content approach, and the results were presented as themes along with participant quotations. Five themes emerged to describe measures for continuity of HIV services. The measures included: 1) leveraging the use of mobile phone technology to support ART adherence counseling, psychosocial care, and reminders concerning clinic appointments and referrals; 2) adoption of novel differentiated service delivery models for ART like the use of motorcycle taxis and introduction of an individualized ART delivery model for patients with non-disclosed HIV status; 3) scale-up of existing differentiated service delivery models for ART, namely multi-month dispensing of antiretroviral drugs (ARVs), fast-track ARV refill, home-based ARV refill, peer ART delivery, use of community pharmacy model, and community client-led ART delivery model; and, 4) reorientation of health facility functioning to the COVID-19 pandemic restrictions characterized by the use of nearby health facilities for ARV refill and viral load monitoring, transportation of healthcare providers and flexible work schedules and reliance on shift work. We found several measures were adopted to deliver HIV care, treatment, and support services during the COVID-19 pandemic restrictions in Kampala, Uganda. We recommend the scale-up of the new measures for service continuity in the post-COVID-19 period.